Strong Genetic Structure Observed in Primulina danxiaensis, a Small Herb Endemic to Mount Danxia With Extremely Small Populations - Chen, Sufang; Guo, Wei; Chen, Zaixiong; Liao, Wenbo; Fan, Qiang (Frontiers in Genetics, 2021)
Danxia landform occurring sporadically in southern China is a unique type of petrographic geomorphology. It has nurtured about 400 rare or threatened plant and animal species, whose diversity, endemism, and conservation have called increasing scientific and public attentions. Among them, Primulina danxiaensis (W. B. Liao, S. S. Lin, and R. J. Shen) W. B. Liao and K. F. Chung is a tiny perennial grass species recorded only in Mount Danxia, a natural World Heritage Site as part of China’s Danxia. In this study, restriction site-associated DNA sequencing (RAD-seq) was performed to investigate genetic diversity among these 12 populations of P. danxiaensis. A total of 432,041 variant sites were detected in 84,779 loci across 94 samples. The expected heterozygosity (HE) ranged from 0.017 to 0.139. Bottleneck signals were detected in most populations, Tajima’s D tests showed that most loci could be under recent positive selection, and one of the six positively selected loci identified by BayeScan was annotated as tRNAGlu, which may contribute to the species’ adaptation to shady environment. STRUCTURE analysis and phylogenetic tree showed that the 12 populations of P. danxiaensis could be divided into four gene pools (clades) corresponding to their geographic locations, and significant correlation was observed between genetic and geographic distances. Our study demonstrated that P. danxiaensis maintained a middle level of genetic diversity and strong population structure; geographic distance could be an important factor limiting gene flow among populations of P. danxiaensis, which were only sporadically recorded in Mount Danxia.